أثر إستراتيجيتي دورة التعلم المعدلة ونصوص تغيير المفاهيم في فهم طلاب الصف التاسع الأساسي لمفاهيم البناء الضوئي والتنفس في النباتات - الخوالدة، سالم عبدالعزيز عواد (جامعه دمشق - كليه التربية, 2017)
The purpose of this study is to investigate the effects of the modified learning cycle 5E, and conceptual change texts, and traditional instructions on 9th grade students' understanding of photosynthesis and respiration in plants. Using information collected through interviews with Biology teachers and related literature, the Photosynthesis and Respiration in Plants Concepts Test was developed, and administered as a pre-test, post-test to a total of (102) 9th grade students in 3 sections at a school in an urban area. The sections were randomly assigned as a control and two experimental groups. Students in the first experimental group (n = 33) received modified learning cycle 5E instruction. Students in the second experimental group (n = 34) received conceptual change text instruction, and students in the control group (n = 35) received traditional instruction. Attitudes towards science and pretest scores were used as covariates. A quasi experimental design utilizing the analysis of covariance showed a statistically significant difference between the experimental and control groups in the favor of experimental groups after treatment. However, no statistically significant difference was found between two experimental groups (5E versus conceptual change text instruction). A number of recommendations were derived from the findings of this study.
هدفت هذه الدراسة إلى استقصاء أثر استراتيجي دورة التعلم المعدلة 5E، ونصوص تغيير المفاهيم، والطريقة التقليدية في فهم طلاب الصف التاسع الأساسي لمفاهيم البناء الضوئي والتنفس في النباتات. وتم تطوير اختبار مفاهيم البناء الضوئي والتنفس في النباتات المستخدم في هذه الدراسة، اعتماداً على البيانات التي تم الحصول عليها من خلال المقابلات، التي أجريت مع عدد من معلمي الأحياء في مرحلة التعليم الأساسي، ومراجعة الأدب التربوي ذي الصلة، حيث تم تطبيقه كاختبار قبلي وبعدي على عينة مكونة من (102) من طلاب الصف التاسع الأساسي موزعين في ثلاث شعب في إحدى المدارس الأساسية للذكور في منطقة مدنية. وقد وزعت هذه الشعب عشوائيا لتكيل المجموعة الضابطة والمجموعتين التجريبيتين. أما المجموعة التجريبية الأولي (ن =33) فقد تم تدريسها بطرقية دروة التعلم المعدلة 5E، ودرست المجموعة التجريبية الثانية (ن =34) باستخدام نصوص تغيير المفاهيم، في حين جرست المجموعة الضابطة (ن= 35) بالطريقة الاعتيادية (التقليدية). وتم استخدام متغيرا الاتجاهات نحو العلوم، وعلامات اختبار مفاهيم البناء الضوئي والتنفس في النباتات القبلي كمتغيرين مصاحبين. وأشارت نتائج الدراسة إلى تفوق المجموعتين التجريبيتين (مجموعة دورة التعلم المعدلة 5E، ومجموعة نصوص تغيير المفاهيم) وبدلالة إحصائية على المجموعة الضابطة (الاعتيادية) في فهم مفاهيم البناء الضوئي والتنفس في النباتات. كما أظهرت النتائج عدم وجود فروق دالة إحصائيا بين المجموعتين التجريبيتين في فهم مفاهيم البناء الضوئي والتنفس في النباتات، وقد خلصت الدراسة إلى عدد من التوصيات في ضوء النتائج.
Keywords: استراتيجيات التعلم; تغيير المفاهيم; البناء الضوئي; التعلم المعدلة